2001
DOI: 10.4049/jimmunol.167.10.5795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CDw92 as a Member of the Choline Transporter-Like Protein Family Regulated Specifically on Dendritic Cells

Abstract: CDw92 is a 70-kDa surface protein broadly expressed on leukocytes and endothelial cells. In this manuscript, we present the molecular cloning of the CDw92 molecule by using a highly efficient retroviral expression cloning system. Sequence analysis of the CDw92 cDNA revealed a length of 2679 bp. The 1959-bp open reading frame encodes a protein of 652 amino acids. Computational analysis of the CDw92 protein sequence indicates 10 transmembrane domains, three potential N-linked glycosylation sites, and an amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 39 publications
5
42
0
Order By: Relevance
“…The last 21 bp (1,994 -2,015 bp) of CTL1a encode the COOH-terminus peptide A 651 SGASSA 657 , whereas the last 12 bp of CTL1b encode L 651 KKR 654 ( Fig. 1) (60,72).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last 21 bp (1,994 -2,015 bp) of CTL1a encode the COOH-terminus peptide A 651 SGASSA 657 , whereas the last 12 bp of CTL1b encode L 651 KKR 654 ( Fig. 1) (60,72).…”
Section: Resultsmentioning
confidence: 99%
“…mCTL1 protein is predominantly expressed in skeletal muscle and is barely detectable in other tissues (73). rCTL1 mRNA is found solely in the colon, ileum, brain, and spinal cord (40,60), whereas hCTL1 protein, also named CDw92, is initially detected as a cell surface antigen in monocytic and dendritic cells (72).…”
mentioning
confidence: 99%
“…For the identification of such structures we combined classical hybridoma technology with a selective functional screening approach and a highly efficient retroviral expression cloning strategy, which we have recently established (10,11). With this approach, we discovered an accessory receptor on DC that promotes the induction and maintenance of anergy in T cells.…”
Section: B7-h1 (Programmed Deathmentioning
confidence: 99%
“…To identify the molecule recognized by the mAb DF272, we used a retroviral expression cloning approach (10,11). A cDNA library from monocyte-derived DCs had been constructed in the retroviral vector CRU5-IRES-GFP featuring CMV promoter driven expression of the cDNA along with GFP expression from an internal ribosomal entry site.…”
Section: The Mab Df272-defined Cell Surface Molecule Is B7-h1 (Pd-l1)mentioning
confidence: 99%
“…Interand intracellular choline transport are mediated by different transporter systems such as the polyspecific organic cation transporters, the high-affinity choline transporters (CHTs) and the intermediate-affinity choline transporter-like proteins (CTLs) 2,3 . CHT1 is almost exclusively expressed in cholinergic neurons and is required for the reuptake of choline from the synaptic cleft into presynaptic neurons [4][5][6][7] , whereas the ubiquitous expression of CTL1/SLC44A1 in mammalian tissues suggest that choline transport is also required for more general cellular functions like phospholipid biosynthesis 3,[8][9][10][11][12] . Interestingly, it has recently been suggested that CTL4/SLC44A4 may have a specific role in the synthesis of non-neuronal acetylcholine 13 .…”
mentioning
confidence: 99%